2007
DOI: 10.1007/s00244-007-9000-x
|View full text |Cite
|
Sign up to set email alerts
|

A Real-Time PCR Method for the Quantification of the Two Isoforms of Metallothionein in Lake Trout (Salvelinus namaycush)

Abstract: Metallothioneins (MTs) are low-molecular-weight proteins whose physiologic roles are the regulation of essential metals Cu and Zn, sequestration of heavy metals, and free radical scavenging. Induced production of MTs in a wide variety of organisms exposed to heavy metals has made them popular exposure indicators. While it has been postulated that the three different isoforms of MT play different physiologic roles, methods to discern induction separately have not been available. The development of real-time pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 38 publications
1
2
0
Order By: Relevance
“…Moreover, Costa et al (2010) showed that the levels of MT decreased in the liver of mature male fish (Rhamdia quelen) exposed to the highest E2 dose with a higher E2 level in plasma. Previous studies showed that E2 or other estrogenic compounds might inhibit MT expression by reducing free intracellular Zn being available to bind to the metal responsive elements in the promoters of MTs during Vtg synthesis (Olsson et al, 1995;Gerpe et al, 2000;Werner et al, 2008). In the present study, MT mRNA expression was also significantly inhibited in the livers of mosquitofish exposed to P or T alone.…”
Section: Modulation Of Mt Gene Expressionsupporting
confidence: 64%
See 1 more Smart Citation
“…Moreover, Costa et al (2010) showed that the levels of MT decreased in the liver of mature male fish (Rhamdia quelen) exposed to the highest E2 dose with a higher E2 level in plasma. Previous studies showed that E2 or other estrogenic compounds might inhibit MT expression by reducing free intracellular Zn being available to bind to the metal responsive elements in the promoters of MTs during Vtg synthesis (Olsson et al, 1995;Gerpe et al, 2000;Werner et al, 2008). In the present study, MT mRNA expression was also significantly inhibited in the livers of mosquitofish exposed to P or T alone.…”
Section: Modulation Of Mt Gene Expressionsupporting
confidence: 64%
“…However, MT gene expression was affected by metals (Rhee et al, 2009), chemicals stressors (Gerpe et al, 2000;Werner et al, 2003) and other factors including age, sex and tissue type (Rhee et al, 2009). Although MT genes have been cloned and their expression has been studied in a number of fish species in response to heavy metals, relatively little is known about how those genes are affected by natural or synthetic hormones (Gerpe et al, 2000;Werner et al, 2008;Rhee et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…X-ray diffraction results together with NMR data have established that the metals are tetrahedrally coordinated in two isolated domains in mammalian Cd-7-MT and Zn-7-MT, and recently, combination of 113 Cd NMR, CD and mass spectrometry showed that domain of MT was capable of binding more than 5 Cd 2+ ions [33]. mRNA RT-PCR human peripheral blood lymphocytes [234] semi-quantitative RT-PCR rat testes and liver (Cd injection) [235] RT-PCR mouse cerebral cortex [236] HPLC-ICP-TOF-MS cytosols of gibel carp [141] RT-PCR ,Western blotting AML-2 cell line [237] CE horse kidney [238] MT 1 CE-ICP rabbit liver [239] mRNA QRT-PCR in situ prostate tissue [240] real-time PCR HeLa cells [241] 2D micro HPLC-ICP-MS RT-PCR isoform-specific knockdown cells [142] saturation with cadmium chloride, ion-exchange HPLC, Western blot AAS-ICP human placenta [242] Immunohistochemical staining Real time RT-PCR, immunoblot human breast and the MCF-10A cell line [243] ELISA in plasma of humans and experimental animals (rabbit, mouse rat) [244] SDS-PAGE, Western blot immunofluorescence staining prostate cells (BPH, PC-3 and HPR-1 cells) [48] RT-PCR agarose gel electrophoresis CD61 + megakaryocytes [245] real-time PCR liver tissue of lake trout [246] cadmium-hemoglobin assay real-time RT-PCR liver and kidney tissue, blood of human and rats [247] tryptic digestion, MALDI-TOF/TOF MS RWPE-1 cells derived from normal human prostate epithelium [197] Western blotting superoxide dismutase 1 transgenic (SOD1 Tg) mouse [248] RT-PCR and in situ hybridisation hippocampus of old rats [249] quantitative real-time RT-PCR breast cancer cell lines [250] MT 1 and 2 real-time RT-PCR keloid keratinocytes [251] semi-quantitative RT-PCR -densitometry scanning ELISA AAS testicular interstitial cells (Sprague-Dawley rats) [36] CZE cytosol of the pancreas and liver in mice [124] anion-exchange HPLC, RP-HPLC MALDI-TOF-MS rabbit liver [252] RT-PCR bone tissue of rats [253] RT-PCR dental pulp of rat incisors [254] immunohistochemistry hyperplastic...…”
Section: Metallothionein Structurementioning
confidence: 99%